Epidemiological trends and age-period-cohort effects on ischemic stroke burden across the BRICS-plus from 1992 to 2021 - Fangqun Cheng; Peiyu Cheng; Shudong Xie; Hailing Wang; Ying Tang; Ying Liu; Zhuo Xiao; Guixiang Zhang; Guangxiong Yuan; Ke Wang; Can Feng; Ying Zhou; et al. (BMC Public Health)
Abstract Background Ischemic stroke, accounting for 85% of stroke cases, leads to severe disabilities and increased mortality. Its global incidence rose by 87.55% from 1990 to 2019, posing significant health and economic burdens. The BRICS-plus nations—Brazil, Russia, India, China, South Africa, and five others—represent a large global population, presenting unique public health challenges. This study aims to evaluate the epidemiological trends and variations in the burden of ischemic stroke across BRICS-plus nations in a timely manner. Methods Data on the number, all-age rate, age-standardized rate, and relative change in ischemic stroke disability-adjusted life years (DALYs) from 1992 to 2021 within BRICS-plus were obtained from the Global Burden of Disease Study (GBD) 2021. Relationships between the DALYs rate and the Socio-demographic Index (SDI) were evaluated using Pearson correlation analyses. Additionally, age-period-cohort modeling was employed to estimate net drift, local drift, age, period, and cohort effects over the past three decades. Results From 1992 to 2021, total DALYs due to ischemic stroke increased by 47.14%, while the age-standardized DALYs rate decreased by 33.79%. All BRICS-plus countries exhibited a declining trend in the age-standardized DALYs rate over the past three decades. Egypt reported the highest age-standardized DALYs rate (2,462.60 per 100,000 population) in 2021, whereas the most substantial reduction of 59.37% was observed in Brazil. The annual net drift in the ischemic stroke DALYs rate ranged from -3.04% for Brazil to -0.48% for Egypt among the ten countries. A significant positive correlation was observed between the DALYs rate of ischemic stroke and SDI values. Countries exhibited similar age effect patterns, with an increasing risk of DALYs rate with advancing age. Period and cohort effects highlighted declines in observed nations, indicating improved ischemic stroke management strategies. Conclusion The burden of ischemic stroke showed an overall declining trend across the BRICS-plus from 1992 to 2021, but persistent health inequalities between these countries were driven by socioeconomic disparities. Furthermore, it emphasizes the necessity for targeted interventions across age, period, and cohort dimensions to address the distinct challenges posed by ischemic stroke in these rapidly developing countries.